Mathematical Modeling of Stunting with the Influence of Nutritional Intervention - Himmah, Elok Faiqotul; Kaestria, Rommi; Riana, Riana (JTAM (Jurnal Teori dan Aplikasi Matematika), 2025)
The high number of stunting in Central Kalimantan with a prevalence that is still quite far from the WHO threshold, which is 26.9%, requires serious handling from the Central Kalimantan Provincial Government. Through the stunting reduction acceleration program, the government is targeting the prevalence of stunting in Central Kalimantan to decrease to 15.38% by 2024. The purpose of this study was to build a mathematical model to determine the dynamics of stunting events in Central Kalimantan with the influence of nutritional interventions. This model will be used to predict changes in stunting prevalence over time, and evaluate the impact of nutritional interventions on reducing stunting. This is a mixed method research that combines quantitative and qualitative approaches. with a mathematical modelling approach. The research method used in this study is a literature study with data collection techniques through semi-structured interviews with sources from the Health Office, Bappedalitbang and BKKBN which are included in the TPPS of Central Kalimantan, and also the BPS of Central Kalimantan. The data collected includes the prevalence of stunting, types and coverage of nutritional interventions, factors that influence stunting in Central Kalimantan, the nutritional status of toddlers, and indicators of nutritional interventions successstunting prevalence. Model simulation with Python programming shows the effectiveness of the intervention in preventing stunting and helping toddlers at risk of stunting to achieve normal nutritional status. Nutritional interventions have successfully reduced the prevalence of stunting in Central Kalimantan by 3.16% and increased the number of toddlers at risk of stunting who managed to achieve normal nutritional status after receiving nutritional interventions by 7%. It can be concluded that early intervention in toddlers at risk of stunting is very important to prevent stunting, and targeted intervention in stunted toddlers is also needed to accelerate recovery and reduce the overall prevalence of stunting.